Investigating experiences of the infidelity partner: Who is the "Other Man/Woman"?. (October 2015) - Weiser, Dana A.; Weigel, Daniel J.
Highlights: We describe the experiences of the infidelity partner (i.e., the other man/woman). Low agreeableness was associated with being an aware infidelity partner. Low agreeableness was associated with a lower likelihood of revealing transgression. Anxious attachment and sociosexuality associated with being infidelity partner. Abstract: Little research has explored infidelity relationships from the perspective of the infidelity partner (i.e. the other man/woman to an exclusive romantic relationship) or explored the personality profiles of these individuals. Participants ( n = 180) completed an online survey. Our findings indicate that most infidelity partners initially do not know they are engaging in infidelity but less than half ended the relationship upon learning of the infidelity. Low agreeableness appears to be a core trait to help explain why some individuals are willing to be an infidelity partner and conceal the transgression. Individuals higher on anxious attachment and an unrestricted sociosexual orientation appear to be more likely to be infidelity partners, although this finding must be cautiously interpreted. As a third party is necessary to engage in infidelity, knowing more about the infidelity partner is essential to furthering the infidelity literature.